A Single-Center Clinical Study to Evaluate Shenxiong Glucose Injection Combined with Edaravone in the Treatment of Acute Large-Area Cerebral Infarction. (30th June 2021) - Li, Zongqin; Rong, Xiaoxia; Luo, Jun; Zeng, Tao; Huang, Pan; Xu, Xuejie
Abstract : Objectives . To investigate the clinical efficacy and safety of Shenxiong glucose injection combined with edaravone in the treatment of acute large-area cerebral infarction. Methods . 156 patients with acute large-area cerebral infarction admitted to our hospital from July 2015 to January 2017 were included in the analysis. The patients were randomly divided into experimental (78 cases) and control (78 cases) groups. Patients in the experimental group were given a 30 mg injection of edaravone in 100 ml of 0.9% sodium chloride solution by intravenous drip, twice a day within 30 minutes and a daily 200 ml injection of Shenxiong glucose by intravenous drip. Patients in the control group were given a 30 mg edaravone injection in 100 ml of 0.9% sodium chloride solution by intravenous drip, twice a day, and the drip was completed within 30 minutes. Patients in both groups were treated for 2 weeks. The levels of fibrinogen (FIB), D-dimer, interleukin 6 (IL-6), P-selectin (CD62P), and hypersensitive C-reactive protein (hs-CRP) were evaluated in the two groups of patients. Neurological disability was evaluated using the modified Rankin scale (mRS) and the neurological deficit score (National Institute of Health Stroke Scale, NIHSS). Adverse reactions to the treatments were also recorded. Results . No significant differences in age, gender, medical histories, and blood biochemical indices were observed between the two groups before treatment (P > 0.05 ). After treatment, the levels of FIB, D-dimer, IL-6, CD62P, and hs-CRP were significantly lower following treatment and compared to the control group (P < 0.05 ). Also, the mRS and NIHSS scores were significantly lower after treatment and compared with the control group (P < 0.05 ). The total effective rate of the treatment in the experimental group was significantly higher compared to the control group (P < 0.05 ). During the treatment period, no obvious adverse reactions were observed in the two groups of patients. Conclusions . In addition to the routine basic treatment of acute large-area cerebral infarction, the addition of Shenxiong glucose injection combined with edaravone injection can improve platelet aggregation and reduce inflammation by affecting P-selectin, D-dimer, and FIB. This treatment approach promotes the recovery of nerve defect function without obvious adverse reactions in patients with acute large-area cerebral infarction.